Coveting thy Neighbour's Beer: Intergovernmental Agreements Dispute Settlement and Interprovincial Trade Barriers - Culat, Didier (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1992)
Recent developments have led the governments of Canada to negotiate intergovernmental agreements lowering interprovincial trade barriers. Those agreements include a new element; a dispute settlement mechanism. The dispute settlement mechanism included in the recently concluded Beer Marketing Agreement was inspired by that found in the General Agreement on Tariffs and Trade. This article conducts a comparative analysis of these dispute settlement mechanisms and recommends, on the basis of the international model's experience, refining the process in the Beer Marketing Agreement to ensure an effective dispute settlement mechanism.